Antimicrobial nature and healing behavior of plasma functionalized polyester sutures. (May 2017) - Anjum, Sadiya; Gupta, Amlan; Sharma, Deepika; Kumari, Shanti; Sahariah, Plabita; Bora, Jutishna; Bhan, Surya; Gupta, Bhuvanesh
This study deals with the development of bioactive poly(ethylene terephthalate) surgical suture by adopting the immobilization route with bioactive nanogels and chlorhexidine. Carbon dioxide plasma was used for the generation of carboxyl functionality on poly(ethylene terephthalate) surface for the immobilization of the bioactive components. The nanosilver nanogel was prepared using polyethylene glycol which helps in the reduction of silver ions into nanosilver as well as the stabilization of nanoparticles. The particle size of the nanogels, as evaluated by high-resolution transmission electron microscopy, was observed to be in the range of 10–50 nm. Surface functionalization of poly(ethylene terephthalate) filament was observed by attenuated total reflectance measurements and mechanical studies were investigated by Instron. Elemental analysis and surface topography were carried out by energy dispersive X-ray and atomic force microscopy. The cumulative release of silver from the dressing was found to be 68% of the total loading after 72 h. Coated sutures have excellent antimicrobial activity against both Escherichia coli and Staphylococcus aureus . In vivo wound healing and histopathology studies were carried out over a period of 72 h for skin wounds created on Swiss albino mice. Fast healing was observed in nanogel-treated wounds without any inflammatory effects on the newly generated skin. These sutures offer improved healing along with excellent antimicrobial properties and appear to be promising material against surgical infection.